2019
DOI: 10.4274/tjh.galenos.2018.2018.0230
|View full text |Cite
|
Sign up to set email alerts
|

Different Presentations of Patients with Transcobalamin II Deficiency: A Single-Center Experience from Turkey

Abstract: Objective: Transcobalamin II deficiency is a rare autosomal recessive disease characterized by decreased cobalamin availability, which in turn causes accumulation of homocysteine and methylmalonic acid. The presenting clinical features are failure to thrive, diarrhea, megaloblastic anemia, pancytopenia, neurologic abnormalities, and also recurrent infections due to immune abnormalities in early infancy. Materials and Methods: Here, we report the clinical and laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…In patients with TC deficiency, deletions are the most common variant, with insertions and variants at splicing sites rarely found. The majority (about 80%) of patients carried homozygous variants, while only a minority had compound-heterozygous variants (Schiff et al, 2010;Trakadis et al, 2014;Bartakke et al, 2015;Chao et al, 2017;Li and Goubeaux, 2017;Yildirim et al, 2017;Ünal et al, 2019). In this study, a pair of compound-heterozygous variants in TCN2 gene were identified, which is a very valuable case of TC deficiency.…”
Section: Treatment and Prognosismentioning
confidence: 85%
See 2 more Smart Citations
“…In patients with TC deficiency, deletions are the most common variant, with insertions and variants at splicing sites rarely found. The majority (about 80%) of patients carried homozygous variants, while only a minority had compound-heterozygous variants (Schiff et al, 2010;Trakadis et al, 2014;Bartakke et al, 2015;Chao et al, 2017;Li and Goubeaux, 2017;Yildirim et al, 2017;Ünal et al, 2019). In this study, a pair of compound-heterozygous variants in TCN2 gene were identified, which is a very valuable case of TC deficiency.…”
Section: Treatment and Prognosismentioning
confidence: 85%
“…It is well known that early and proper treatment is crucial for achieving optimal outcomes (Yildirim et al, 2017;Ünal et al, 2019;Zhan et al, 2020). Most studies showed that early and aggressive treatment, which includes parenteral or high-dose…”
Section: Treatment and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Later, when transcobalamin defect and its associated increased homocysteine level was suspected, plasma homocysteine level was measured using a separate specific test. Less than 60 patients and 50 TCN2 variants have been reported worldwide in which many cases were reported from regions with a high rate of consanguinity, including Turkey [1,2,[11][12][13][14]. To our knowledge, the present patient is the first case report from a Southeast Asian country with a novel TCN2 variant, c.428-2A > G. The variant was subsequently submitted to ClinVar database and now is accessible using a number SCV001981507 (https:// www.…”
Section: Discussionmentioning
confidence: 99%
“…The name “V”EXAS syndrome stems from “vacuoles” in myeloid and erythroid cells, but not in T lymphocytes, B lymphocytes, or fibroblasts ( 11 ). Of note, myeloid and erythroid vacuolization is not specific to VEXAS syndrome, but has been described in other disorders, including copper deficiency ( 39 ), acute myeloid leukemia ( 40 ), Menkes disease ( 41 ), and transcobalamin II deficiency ( 42 ).…”
Section: Clinical Phenotypes Of Vexas Syndromementioning
confidence: 99%